Rasionalitas dan Moralitas dalam Pembelajaran Ekonomi - Mayasari Mayasari (Universitas Batanghari Jambi, 2021)
Economic behavior is the actions or reactions of an object in the form of both rationality, morality, lifestyle, efficiency in consumptive activities, and effectiveness in productive activities. In this paper, the actions to be discussed, analyzed, and studied are actions about rationality and morality in economic learning. In essence, rationality in economic learning teaches students to act rationally in taking economic action. The result of this act of rationality forms students to become materialists, to have economic value, and to maximize the benefits of rational thinking. However, not all economic learning is rationalized because in economic learning there is economic morality that can educate students to be more moral to become economicus man (economic man). Morality relates to one's actions in social relationships, which emphasizes one's concern for the existence of others.